Whose Land is Lapland? : The Nellim Case : A Study of the Divergent Claims of Forestry, Reindeer Herding and Indigenous Rights in Northern Finland - Moran, Daniel James (Helsingfors universitet, 2012)
This study analyzes the various interests associated with the Nellim Case; that is, of the Sámi Paadar brothers and the Nellim group of the Ivalo Reindeer Herding Cooperative, within the Nellim community and the Inari municipality of Finland. Until the settlement agreements in 2009 and 2010, there has been an ongoing conflict between the Finnish state administered forest management department Metsähallitus and both Sámi and non-Sámi reindeer herders over the amount and location of the old-growth forests to be included as part of the annual timber harvest within the Sámi domicile area. This reindeer herding and forestry conflict in northern Finland illustrates how the Sámi are embroiled in a struggle over recognition of their rights as indigenous people to claimed land and resources stemming from their traditional lands. While the Finnish state signed the United Nations Declaration on the Rights of Indigenous Peoples of 2007, and has promised to ratify the binding 1989 International Labour Organization Convention 169 Concerning Indigenous Peoples in Independent Countries (ILO 169), little has actually been done towards ratification of the ILO convention or implementation of norms required by the UN declaration. At the root of the problem for the Sámi is the fundamental desire for some form of control, decision-making power, or self-determination; one that includes their own customs and is recognized by the majority society. Finland, through its historical and recent actions and inactions, has failed to ascribe the required level of self-determination to the Sámi, despite making proud claims to be a bastion of human rights and a multicultural society. Utilizing case study methodology, a critical analysis was undertaken on interviews and press releases by various interests related to the land conflict between reindeer herders and old-growth forestry loggers in Nellim, Finland. The justifications of the claims made by the actors in their interviews were analyzed using a form of Public Justifications Analysis, in ...